Adoption of sustainable land and water management practices and their impact on crop productivity among smallholder farmers in sub-Saharan Africa - Mangole, Cool Dady; Maina, Charles Mbogo; Mulungu, Kelvin; Tschopp, Maurice; Harari, Nicole; Suresh, Roopa; Kassie, Menale (Elsevier, 2025)
Land degradation and water challenges threaten sub-Saharan Africa's agricultural productivity and food security. This study uses panel secondary data from the World Bank Living Standards Measurement Study-Integrated Surveys on Agriculture project to evaluate land degradation variations, the adoption of sustainable land and water management (SLWM) practices, and their impacts on crop yields among smallholder farmers in four sub-Saharan African countries: Tanzania, Malawi, Uganda, and Ethiopia. The study used a high-dimensional fixed effects model to control for time-invariant unobserved and time-varying observed household and plot-level confounders. The results indicate that while many households experienced land degradation and water problems, SLWM adoption has decreased over the past ten years. The study finds that household socioeconomic characteristics, extension services and social networks, plot-level farm characteristics (i.e., soil types, soil fertility, slope, plot tenure, and farm size), land degradation, and climate-related variables influence smallholder farmers' adoption of SLWM practices. Further, the adoption of SLWM practices leads to significant increases in crop yields for most practices and countries, particularly when compared to other degraded plots planted with the major crop in each country. These findings highlight the need for targeted interventions to improve farmers' access to tailored agricultural extension services and establish secure land tenure systems to enhance the adoption of SLWM practices in most countries. Further research is needed to identify effective strategies for promoting the adoption of SLWM practices and understand the challenges to their implementation. Improving systems such as extension, cooperatives, and digital tools to deliver timely and efficient information about SLWM practices and secure land tenure in some contexts can improve the adoption of these practices.